Effect of dietary supplementation with l-carnitine, chromium, and selenium on the performance of finishing pigs - Caio Abércio da Silva; Arlan Marcos Lorenzetti; Silvonei Conte; Cleandro Pazinato Dias; Marco Aurélio Callegari; Kelly Lais de Souza; Carlos Rodolfo Pierozan; Luciana Foppa (Semina: Ciências Agrárias, 2019)
This study aimed to assess the combined effect of L-carnitine, chromium propionate, and organic selenium in the diet of pigs at the finishing stage in commercial farms on performance parameters. The sample included 5,456 female and castrated male DB pigs with mean age of 159 days and mean initial weight of 103.33 ± 4.11 kg. The pigs were split into two treatments in a completely randomized design: the control group, free of growth-promoting dietary additives, and the test group, supplemented with Profitilina® (50 mg L-carnitine, 0.2 mg chromium propionate, and 0.3 mg organic selenium kg-1 of feed) for 30 days prior to slaughter. The outcomes assessed were daily weight gain (DWG), daily feed intake (DFI), feed conversion (FC), and final body weight (FBW). An improved performance according to all parameters (P < 0.001) was seen for the test group (2.58 versus 2.64 g day-1 for DFI; 0.76 versus 0.87g day-1 for DWG; 3.42 versus 3.06 for FC; and 125.7 versus 127.7 kg for FBW). Providing a combined dietary supplementation with L-carnitine, chromium propionate, and organic selenium to finishing pigs was effective at improving weight gain, feed intake, feed conversion, and final weight.